Causal Influence of Anthropogenic Forcings on the Argentinian Heat Wave of December 2013 - Hannart, Alexis (2015)
The Argentinian heat wave of December 2013 was likely caused in part by anthropogenic forcings. These forcings have increased the risk of such an event occurring by a factor of five.